Pengaruh Kegiatan Finger Painting Terhadap Kemampuan Motorik Halus Anak Usia Dini 5-6 Tahun di RA Babussalam Purwasari - Syaadah, Fitriani; Aisyah, Dewi Siti; Putri, Feronica Eka (Jurnal Ilmiah Wahana Pendidikan, 2025)
The aim of this research is to determine the influence of Finger Painting activities on the fine motor skills of young children aged 5-6 years. Through this Finger Painting activity, it is hoped that this research can improve children's fine motor skills. With a sample of 13 children in the 5-6 year group, this research used an experimental method with a one group pretest posttest design in group B RA Babussalam Purwsari. The results of the calculations showed that there was a correlation between x and y variables of - 21,083 and a critical t value ( table t) of 1.728. In this case 1.728 > α (0.05) so H0 is rejected because it is much higher than the significance level of 0.05 and Ha is accepted. So it can be concluded that there is a positive and significant influence from Finger Painting activities on the fine motor skills of young children aged 5-6 years at RA Babussalam Purwasari